Tapa in Ronggowarsito's Serat Pamoring Kawula Gusti (1802-1873): The Convergence of Javanese Mysticism and Islamic Spirituality - Arif Shofiullah; Amat Zuhri; Yusuph Dauda Gambari (Fakultas Ushuluddin dan Humaniora - UIN Walisongo Semarang, 2025)
Tapa, a form of Javanese asceticism, constitutes a longstanding tradition and a central element of spiritual life in Javanese society. This practice is frequently documented in Javanese literary works and is regarded as a significant cultural legacy. The present study analyses the concept of tapa in Raden Ngabehi Ronggowarsito's Serat Pamoring Kawula Gusti, focusing on its relationship to Sufi teachings and its role as a process of spiritual discipline and moral transformation. The data were collected through documentation techniques and analysed using a descriptive-interpretive approach through content analysis. The results revealed that tapa is depicted as a systematic approach to self-discipline and moral refinement, with the objectives of attaining sastra cetha (manifest knowledge) and achieving manunggaling kawula Gusti (union of the servant with God). The text demonstrates parallels with Sufi teachings, including purification of the self (takhallī), cultivation of virtuous character (taḥallī), and the unveiling of veils for divine inspiration (tajallī), ultimately culminating in spiritual union with God, as represented by the concepts of ittiḥād and ḥulūl. Contribution: This study highlights the convergence of Javanese spiritual practices and Sufi teachings through Serat Pamoring Kawula Gusti, revealing how tapa cultivates self-discipline, moral refinement, and spiritual awareness, corresponding to Sufi concepts such as takhallī, taḥallī, and tajallī.